Robótica educacional nas aulas de física - (:unkn) unknown (Universidade Federal de Goiás, 2018)
Nowadays, within the class rooms, many pupils relies just in what has been given to them, memorizing only lists of substances that something is made of – formula. This blinds the students leaving them with no vibrancy - unmotivated - and does not bring them to realize the connection between the subject and experience they could experiment in everyday life. They are not even able to expose what they had studied throughout the course. In meaningful learning, the learner cannot be considered only a container ready to be fill up, he must be able to use and pass ahead what he has just learnt and internalized, in a substantive way rather than arbitrary manner, so as to capture the meanings of educational materials. That is, the apprentice builds his knowledge. Looking forward to enhance the learning of Physics in the High School of the Escola SESI Guiomar de Freitas Costa (Uberlândia/MG), we have used Educational Robotics to stimulate interest in physics and meaningful learning in the students. Educational Robotics allows students to improve an ability to develop hypotheses, investigate solutions, make the best connections and draw conclusions, all with well-distributed and controlled time. In this research, we have reported how a robot was built up and also how it was used allowing the students of the first year of high school of the SESI and the Guiomar de Freitas Costa (Uberlândia/MG) to construct the concepts of average speed, types of movements and launching of projectiles, showing how much this part of the mechanics is present in our daily life. During the activity, students were able to understand the main physical concepts involved in the experiments by actively participating in the class.
Educational robotics in physical lessons
Keywords: Robótica educacional; Aprendizagem significativa; Física; Educational robotics; Significant learning; Physical; CIENCIAS EXATAS E DA TERRA::FISICA